2019
DOI: 10.1021/acsnano.9b01100
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Protein-Responsive Nanophotosensitizer Complex for Enhancing Tumor-Specific Therapy

Abstract: A major challenge in cancer treatment is the development of effective tumor-specific therapeutic methods that have minimal side effects. Recently, a photodynamic therapy (PDT) technique using activatable photosensitizers (aPSs) has shown great potential for cancer-specific treatment. Here, we develop a sequential protein-responsive aPS (PcC4-MSN-O1) that is based on zinc(II) phthalocyanine derivative (PcC4)-entrapped mesoporous silica nanoparticles (MSNs) and a wrapping DNA (O1) as a biogate. Inside the nanost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…developed an interesting nanodot based on the supramolecular self‐assembly of a porphyrin–peptide conjugate and showed that the nanodot has a high PA amplitude and photothermal effect because of the inhibited fluorescence emission and singlet oxygen generation . Inspired by this study and given the usual self‐quenching phenomenon of Pc compounds found in our previous study of Pc photochemistry, we thus speculated that the nanostructured assembly of Pc compounds may be an alternative and effective approach for the development of new contrast agents with good performance in PA imaging and PTT. Our speculation also took into account the fact that Pcs generally have longer absorption wavelengths and higher extinction coefficients than porphyrins, which enable them to be more suitable for a phototheranostic application .…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…developed an interesting nanodot based on the supramolecular self‐assembly of a porphyrin–peptide conjugate and showed that the nanodot has a high PA amplitude and photothermal effect because of the inhibited fluorescence emission and singlet oxygen generation . Inspired by this study and given the usual self‐quenching phenomenon of Pc compounds found in our previous study of Pc photochemistry, we thus speculated that the nanostructured assembly of Pc compounds may be an alternative and effective approach for the development of new contrast agents with good performance in PA imaging and PTT. Our speculation also took into account the fact that Pcs generally have longer absorption wavelengths and higher extinction coefficients than porphyrins, which enable them to be more suitable for a phototheranostic application .…”
Section: Resultsmentioning
confidence: 55%
“…[28][29][30][31][32] Fore xample,Y an et al developed an interesting nanodot based on the supramolecular self-assembly of ap orphyrin-peptide conjugate and showed that the nanodot has ah igh PA amplitude and photothermal effect because of the inhibited fluorescence emission and singlet oxygen generation. [30] Inspired by this study and given the usual self-quenching phenomenon of Pc compounds found in our previous study of Pc photochemistry, [17,18,[33][34][35] we thus speculated that the nanostructured assembly of Pc compounds may be an alternative and effective approach for the development of new contrast agents with good performance in PA imaging and PTT.O ur speculation also took into account the fact that Pcs generally have longer absorption wavelengths and higher extinction coefficients than porphyrins,w hich enable them to be more suitable for ap hototheranostic application. [16][17][18][19][20] Hence,t o prevent random aggregations,w hich are believed to be the main reason for the requirement of extra materials to stabilize and deliver the hydrophobic Pc compounds in previous investigations,a nd to provide ah igher possibility for hostguest interactions,P cS4 bearing anionic substituents and PcN4 bearing cationic substituents were selected for this effort.…”
Section: Resultsmentioning
confidence: 70%
“…developed an interesting nanodot based on the supramolecular self‐assembly of a porphyrin–peptide conjugate and showed that the nanodot has a high PA amplitude and photothermal effect because of the inhibited fluorescence emission and singlet oxygen generation . Inspired by this study and given the usual self‐quenching phenomenon of Pc compounds found in our previous study of Pc photochemistry, we thus speculated that the nanostructured assembly of Pc compounds may be an alternative and effective approach for the development of new contrast agents with good performance in PA imaging and PTT. Our speculation also took into account the fact that Pcs generally have longer absorption wavelengths and higher extinction coefficients than porphyrins, which enable them to be more suitable for a phototheranostic application .…”
Section: Resultsmentioning
confidence: 55%
“…Photodynamic therapy (PDT) utilizes the photosensitizer (PS)-triggered production of cytotoxic reactive oxygen species (ROS) under near-infrared (NIR) laser irradiation to kill tumor cells 12 , 13 , 14 , 15 , 16 . Despite the noninvasive characteristics and superior selectivity, PDT-induced O 2 consumption aggravates tumor hypoxia and limits its beneficial therapeutic outcomes.…”
Section: Introductionmentioning
confidence: 99%